2012
DOI: 10.1111/j.1469-185x.2012.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Pikaia gracilensWalcott, a stem‐group chordate from the Middle Cambrian of British Columbia

Abstract: The Middle Cambrian Pikaia gracilens (Walcott) has an iconic position as a Cambrian chordate, but until now no detailed description has been available. Here on the basis of the 114 available specimens we review its anatomy, confirm its place in the chordates and explore with varying degrees of confidence its relationships to both extant and extinct chordates and other deuterostomes. The body of Pikaia is fusiform, laterally compressed and possesses about 100 myomeres. The head is small, bilobed and bears two n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 84 publications
2
64
0
Order By: Relevance
“…Consistent with this, Atlantic salmon notochord sheath cells (chordoblasts) re-orient metamerically in register with chordacentrum formation (Grotmol et al, 2003), correlating with their segmental expression of alkaline phosphatase activity . Moreover, whereas there is currently no strong evidence indicating that the notochord was ancestrally segmented (Stern, 1990), a segmented notochord architecture has been tentatively identified in the fossil protovertebrate Pikaia (Conway Morris and Caron, 2012). The recent suggestion that the notochord evolved from contractile axial mesoderm cells with segmental connections to transverse muscles in a bilaterian ancestor (Lauri et al, 2014) adds further credence to this view.…”
Section: Segmental Patterningmentioning
confidence: 71%
“…Consistent with this, Atlantic salmon notochord sheath cells (chordoblasts) re-orient metamerically in register with chordacentrum formation (Grotmol et al, 2003), correlating with their segmental expression of alkaline phosphatase activity . Moreover, whereas there is currently no strong evidence indicating that the notochord was ancestrally segmented (Stern, 1990), a segmented notochord architecture has been tentatively identified in the fossil protovertebrate Pikaia (Conway Morris and Caron, 2012). The recent suggestion that the notochord evolved from contractile axial mesoderm cells with segmental connections to transverse muscles in a bilaterian ancestor (Lauri et al, 2014) adds further credence to this view.…”
Section: Segmental Patterningmentioning
confidence: 71%
“…Lack of sediment fissility and difficulties of preparation often make exposure of the fossil (especially at either end) difficult. Specimens were studied using a range of photographic techniques commonly employed for this type of material 9 . Pictures of both parts and counterparts were merged in Adobe PhotoshopCS6 using the 'apply image' function and 'darken' blending mode (Fig.…”
Section: Methods Summarymentioning
confidence: 99%
“…Although we need to be careful not to overinterpret the anatomy of soft-bodied fossils, we cannot assume that because features decay rapidly in experiments, they can never be fossilized, particularly if the fossil evidence itself is compelling. Animals that lack an extracellular cuticle, such as the soft-bodied mollusc Odontogriphus, [98] enteropneusts [59] and the chordate Pikaia [55] are preserved in the Burgess Shale, and chaetognaths are preserved in both the Burgess Shale [99] and Chengjiang biotas. [100] Although the body outlines of fossil chaetognaths are poorly defined, [100] those of Odontogriphus, Spartobranchus, Oesia, and Pikaia are clearly preserved, indicating that structures that lack the extracellular materials in cuticles nonetheless survive in Burgess Shale-type deposits (contra [101] ).…”
Section: Using Decay As a Guide To Preservation Can Compromise The Inmentioning
confidence: 99%
“…[51] The same decay experiments allowed the chevron-shaped structures in Conopiscius, a Carboniferous chordate, to be interpreted as myomeres rather than external scales, and also indicated that a decay-resistant cuticle was not necessarily present in Pikaia from the Burgess Shale. [51,55] Decay in seawater has now been monitored in a range of taxa in laboratory experiments (see Table S1, Supporting Information): anthozoans, [56] annelids, [48] chaetognaths, [57] priapulids, [18] onychophorans, [17] pterobranchs, [58] enteropneusts, [59] nonvertebrate chordates, [20] and cyclostomes. [60] Thus the sequence of character loss has been determined for taxa representing most clades of eumetazoans.…”
Section: Boxmentioning
confidence: 99%